2016
DOI: 10.1039/c5gc02187a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and enzymatic modification of sophorolipids

Abstract: The significance of renewable resources within the chemical industry is constantly increasing. In the pursuit of sustainability, they serve as alternatives for fossil resources whose supply is limited and who have a major impact on the environment. Due to their complex structure and divergent biological activities, sophorolipids are interesting renewable resources. Unfortunately, industrial applications of natural sophorolipids are limited because of their high production cost. Therefore, chemical and enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 82 publications
2
66
0
Order By: Relevance
“…For example, Lang et al reported that the inhibitory effect of SL against Gram-positive bacteria follows the order of diacetylated SL > monoacetylated SL > nonacetylated SL (Lang et al, 1989). The acidic form of SL was earlier shown to have higher antimicrobial activity than the lactonic form (Gross and Shah, 2004;Kim et al, 2002), but was contradicted in later studies by Delbeke et al (2016). SL containing a STA (18:0) moiety were found to be more effective in inhibiting the growth of skindegrading and hide-degrading bacteria than SL with either an OLA (18:1) or a PAM (16:0) moiety (Solaiman et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Lang et al reported that the inhibitory effect of SL against Gram-positive bacteria follows the order of diacetylated SL > monoacetylated SL > nonacetylated SL (Lang et al, 1989). The acidic form of SL was earlier shown to have higher antimicrobial activity than the lactonic form (Gross and Shah, 2004;Kim et al, 2002), but was contradicted in later studies by Delbeke et al (2016). SL containing a STA (18:0) moiety were found to be more effective in inhibiting the growth of skindegrading and hide-degrading bacteria than SL with either an OLA (18:1) or a PAM (16:0) moiety (Solaiman et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…47 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 11 the purity and uniformity of the starting product. 39 For this reason, it is of utmost importance that both the purity and uniformity of the fermentation product are as high as possible and that enough starting material is available to enable the generation of considerable amounts of the chemical derivatives to perform applications tests. Furthermore, scale up of the fermentation procedure and modification steps is necessary to make the synthesis of valuable derivatives feasible on an industrial scale.…”
Section: Determination Of the Antimicrobial Activitymentioning
confidence: 99%
“…20,21 To explore new properties and broaden the application potential of the natural sophorolipids, several chemical derivatives including alkyl esters (better emulsifiers) [22][23][24][25] and polymers 26 have been recently developed, just to cite some. 27 One possible approach consists in modifying the double bond in the C18:1 backbone. 28 Several chemical modification paths were developed by us starting from the diacetylated C18:1 sophorolipid lactone A (Figure 1).…”
Section: Introductionmentioning
confidence: 99%